Role of Toxoplasma surface proteins in host-parasite immune modulation: Toxoplasma surface proteins and host immune modulation - Bakr, Hawri Mustafa (Cellular and Molecular Biology, 2025)
Toxoplasma gondii is an intracellular parasite that evades the host immune system using its surface proteins. These proteins, including SAGs, MICs, and GRA, regulate host immune responses by interacting with immune receptors, modifying immune signaling pathways, and suppressing inflammatory responses. This modulation allows the parasite to survive and replicate within host cells. The study employed various biochemical and immunological methods, such as ELISA, flow cytometry, RT-PCR, Surface Plasmon Resonance (SPR), and co-immunoprecipitation (Co-IP), to assess the effects of these surface proteins on immune responses. Results showed that Toxoplasma surface proteins reduced the production of inflammatory cytokines (e.g., TNF-α) and increased anti-inflammatory cytokines (e.g., IL-10). SPR analyses confirmed direct interactions between parasite proteins and host immune receptors, altering immune-related signaling pathways. These findings emphasize the significant role of Toxoplasma surface proteins in suppressing the immune system and promoting parasite survival and replication. A deeper understanding of these mechanisms could aid in developing new therapeutic strategies and vaccines against toxoplasmosis. Future research could focus on identifying additional signaling pathways and creating targeted interventions.